A Constant-Utility Index of the Cost of Living - Klein, L. R.; Rubin, H. (Review of Economic Studies, 1947)
L. R. Klein, H. Rubin; A Constant-Utility Index of the Cost of Living 1, The Review of Economic Studies, Volume 15, Issue 2, 1 January 1947, Pages 84–87, https: